Penerapan Sapta Pesona Potensi Desa Wisata Petik Jambu di Desa Kebaron Kecamatan Tulangan Kabupaten Sidoarjo - Astrid Eka Wahyu Cahya Megananda; Hasan Ismail (Public Sphere Review, 2023)
Tourism is the sector most affected by the outbreak of the Covid-19 pandemic. This condition occurs all over the world in various sizes and dimensions. The existence of Sapta Pesona, seven conditions that must be applied and disseminated in people's daily lives, can increase the attractiveness and competitiveness of tourism. This refers to the support and role of the community as the host in creating an environment and atmosphere that can encourage the growth and development of the tourism industry through the embodiment of these seven elements. Kebaron Village is one of the villages in Sidoarjo with guava garden tourism sites and is very rich in guava products. In the village of Kebaron in Sidoarjo, various varieties of guava are planted in an area of 5.5 hectares, there are about 1,200 guavas. One of the obstacles to picking guava tourism in Kebaron village is the reduced number of visitors after the Covid-19 pandemic which started in early 2020. Therefore, it is necessary to add and renovate the garden area by adding supporting infrastructure. Based on the analysis with partners, there are several issues that need to be addresse dimmediately.